EVALUASI DAMPAK GOOD CORPORATE GOVERNANCE BADAN USAHA MILIK NEGARA REAL ESTATE BAGI MASYARAKAT KELURAHAN BENOA KECAMATAN KUTA SELATAN KABUPATEN BADUNG (STUDI KASUS PT BALI TOURISM DEVELOPMENT CORPORATION NUSA DUA BALI) - Suryani Dewi, De Vd (CITIZEN CHARTER, 2014)
ABSTRACT Â Good Corporate Governance is generally known as a good system and structure to manage a company in order to increase the value of shareholders and to accomodate the stakeholders such as creditor, supplier, bussines association, consumer, worker, goverment, and wider community. The aim of this research are to know the evaluationÂ impact and obstacles of Good Corporate Governance PT. Bali Tourism Development Corporation (BTDC) for society in Benoa Village, Sub-district of South Kuta, Badung Regency. The result of this research indicated PT.BTDC already applied the concept of Good Corporate Governance in every done activity in order to be a Bali tourism company. The sample of the activity is doing the PKBL (Program Kemitraan dan Bina Lingkungan). PT. BTDC applied 5 principals of GCG; transparency, accountability, responsibility, independency, and fairness on a good scale and appropriate with BUMN regulation which is occurred and can be said has a good social responsibility. Â Keyword: Evaluation, GCG, CSR